An International Economy: Problems and Prospects - Furth, J. Herbert; Myrdal, Gunnar (Econometrica, 1959)
An international economy: problems and prospects , An international economy: problems and prospects , کتابخانه دیجیتال و فن آوری اطلاعات دانشگاه امام صادق(ع)